Safety and efficacy of a GLP-1 and glucagon receptor dual agonist mazdutide (IBI362) 9 mg and 10 mg in Chinese adults with overweight or obesity: A randomised, placebo-controlled, multiple-ascending-dose phase 1b trial. (December 2022) - Ji, Linong; Gao, Leili; Jiang, Hongwei; Yang, Jing; Yu, Lei; Wen, Jie; Cai, Chenghang; Deng, Huan; Feng, Liqi; Song, Baili; Ma, Qingyang; Qian, Lei
Summary: Background: Mazdutide (also known as IBI362 or LY3305677), a novel once-weekly glucagon-like peptide-1 (GLP-1) and glucagon receptor dual agonist, achieved 12-week body weight loss up to 6.4% at doses up to 6 mg in Chinese adults with overweight or obesity. We further explored the safety and efficacy of mazdutide dosed up to 9 mg and 10 mg. Methods: In this randomised, placebo-controlled, multiple-ascending-dose phase 1b trial, we enrolled adults (aged 18-75 years, both inclusive) with overweight (body-mass index [BMI] ≥24 kg/m 2 ) accompanied by hyperphagia and/or at least one obesity-related comorbidity or obesity (BMI ≥28 kg/m 2 ) from five hospitals in China. Eligible participants were randomly assigned (2:1) within each cohort by using an interactive web-response system to receive once-weekly subcutaneous mazdutide or placebo for 12 weeks in the 9 mg cohort (3 mg weeks 1-4; 6 mg weeks 5-8; 9 mg weeks 9-12) and for 16 weeks in the 10 mg cohort (2.5 mg weeks 1-4; 5 mg weeks 5-8; 7.5 mg weeks 9-12; 10 mg weeks 13-16). The participants, investigators, study site personnel involved in treating and assessing participants in each cohort and sponsor personnel were masked to treatment allocation. The primary outcomes were safety and tolerability of mazdutide, assessed from baseline to end of follow-up in all participants who received at least one dose of the study treatment. The secondary outcomes included the change from baseline to week 12 or week 16 in body weight, waist circumference and BMI. This trial is registered with ClinicalTrials.gov, NCT04440345. Findings: Between Mar. 1, 2021 and Mar. 26, 2021, a total of 24 participants were enrolled, with eight randomly assigned to mazdutide and four to placebo in each cohort. One participant receiving mazdutide and two receiving placebo in the 10 mg cohort withdrew consent and quitted the study. No serious adverse event was reported. All treatment-emergent adverse events (TEAEs) were mild or moderate in severity and most commonly-reported TEAEs were upper respiratory tract infection, diarrhoea, decreased appetite, nausea, urinary tract infection, abdominal distension and vomiting. The mean percent change from baseline to week 12 in body weight were −11.7% (SE 1.5) for participants receiving mazdutide in the 9 mg cohort and −1.8% (1.6) for participants receiving placebo (estimated treatment difference [ETD]: −9.8%; 95% confidence interval [CI]: −14.4, −5.3; P  = 0.0002). The mean percent change from baseline to week 16 in body weight were −9.5% (SE 1.7) for participants receiving mazdutide in the 10 mg cohort and −3.3% (1.9) for participants receiving placebo (ETD: −6.2%; 95% CI: −11.5, −0.9; P  = 0.024). In addition, compared with placebo, mazdutide achieved more profound reductions in waist circumference and BMI. Interpretation: Mazdutide dosed up to 9 mg and 10 mg was both well tolerated and showed a favourable safety profile. High-dose mazdutide showed promising 12-week body weight loss, holding great potential for the treatment of moderate-to-severe obesity. A larger and longer phase 2 trial will further evaluate the efficacy and safety of high-dose mazdutide in Chinese adults with obesity. Funding: Innovent Biologics, Inc.